2004
DOI: 10.1016/j.immuni.2004.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Association of Extensive Polymorphisms in the SLAM/CD2 Gene Cluster with Murine Lupus

Abstract: Susceptibility to autoimmunity in B6.Sle1b mice is associated with extensive polymorphisms between two divergent haplotypes of the SLAM/CD2 family of genes. The B6.Sle1b-derived SLAM/CD2 family haplotype is found in many other laboratory mouse strains but only causes autoimmunity in the context of the C57Bl/6 (B6) genome. Phenotypic analyses have revealed variations in the structure and expression of several members of the SLAM/CD2 family in T and B lymphocytes from B6.Sle1b mice. T lymphocytes from B6.Sle1b m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
348
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(356 citation statements)
references
References 50 publications
6
348
2
Order By: Relevance
“…It has been demonstrated that expression of Sle1 is responsible for the increased survival of autoreactive B-cell clones. 26,27 Addition of Sle3 and Sle5 may further lower the threshold for B-cell activation and increase the tendency for autoreactive B cells to proliferate/differentiate upon stimulation by autoantigens. Therefore, the variability of antigen reactivity in different mice of the same strain may be in part due to the stochastic encounters of these B-cell clones with different autoantigens.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that expression of Sle1 is responsible for the increased survival of autoreactive B-cell clones. 26,27 Addition of Sle3 and Sle5 may further lower the threshold for B-cell activation and increase the tendency for autoreactive B cells to proliferate/differentiate upon stimulation by autoantigens. Therefore, the variability of antigen reactivity in different mice of the same strain may be in part due to the stochastic encounters of these B-cell clones with different autoantigens.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with our previous study, 6 in which SLE traits were mapped in (129 Â C57BL/6)F2 wild-type and (129 Â C57BL/6)F2.ApcsÀ/À mice. The linkages were markedly increased when we enlarged the sample size by combining data from the 21 The autoimmune-associated haplotype of the lupus-prone NZM2410 (NZW) strain, named the Slam/Cd2 haplotype 2, is also present in the 129/SvJ mice, 21 indicating that these two strains may share the same pathways leading to loss of peripheral tolerance when in combination with one or more polymorphic genes in the B6 genome. These observations give compelling evidence for the presence of a 129 locus influencing systemic autoimmunity on telomeric chromosome 1 as revealed in the context of B6 genome.…”
Section: Discussionmentioning
confidence: 99%
“…21 This may rule out Fcgr2b as the candidate monocytosis gene. However, Ifi202 is also overexpressed in Bxs2/3 mice 22 and the signalling lymphocyte activation molecule (SLAM) locus is the same haplotype as NZB 23 (unpublished NJ Rogers, SJ Rose and BJ Morley), all of which are strong candidates.…”
Section: Discussionmentioning
confidence: 99%